2017
DOI: 10.1186/s13023-017-0620-6
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal recessive inherited bleeding disorders in Pakistan: a cross-sectional study from selected regions

Abstract: BackgroundAutosomal recessive bleeding disorders (ARBDs) include deficiencies of clotting factors I, II, V, VII, X, XI, XIII, vitamin K dependent clotting factors, combined factor V & VIII, Von Willebrand Disease (vWD) type 3, Glanzmann’s thrombasthenia (GT) and Bernard–Soulier syndrome. Patients with primary bleeding disorders from all the major provincial capitals of Pakistan were screened for ARBDs. Prothrombin (PT), activated partial thromboplastin time (APTT), bleeding time (BT) and fibrinogen levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“… 1 , 3 Pakistan is one of the countries having high rate of consanguineous marriages, so it is expected that RBDs would be more prevalent here as compared to worldwide data, but they largely remain undiagnosed in the region due to lack of specialized diagnostic facilities, lack of public awareness and low clinical suspicion in many cases. 3 , 4 Due to these limitations, there is not much local data regarding frequency and clinical spectrum of these disorders.…”
mentioning
confidence: 99%
“… 1 , 3 Pakistan is one of the countries having high rate of consanguineous marriages, so it is expected that RBDs would be more prevalent here as compared to worldwide data, but they largely remain undiagnosed in the region due to lack of specialized diagnostic facilities, lack of public awareness and low clinical suspicion in many cases. 3 , 4 Due to these limitations, there is not much local data regarding frequency and clinical spectrum of these disorders.…”
mentioning
confidence: 99%
“…A prior study found that factor XI, BSS, and GT deficiencies are all characterized by easy bruising. [20] In our study, seventeen (15.04%) cases had family history of rare bleeding. Frequency of consanguinity was found in 88 (77.9%) cases.…”
Section: Discussionmentioning
confidence: 52%
“…4 Our region is considered to have a high burden of patients with increased transfusion needs like those born with diseases like hemophilia, thalassemia, platelet function defects and others. [11][12][13] Nevertheless, we have a population consisting of a high number of young adults who can be potential blood donors but the barriers like lack of knowledge, myths and misconceptions, and fears about blood donation process are still a blockage towards achieving 100% voluntary blood donation goal. Our study focused to find out these fears among the blood donors coming to a tertiary care facility and we have tried to determine their association with donors' characteristics.…”
Section: Discussionmentioning
confidence: 99%